FAKTOR YANG MELATARBELAKANGI WANITA MELAKUKAN CERAI GUGAT ( Studi Kasus di Kelurahan Parupuk Tabing Kecamatan Koto Tangah Padang Sumatera Barat ) - Oktensis, Saprida - (Pendidikan Sosiologi, 2014)
Base data of Religion Justice office brazes 1 a. Deserts West Sumatra at gets that divorce litigates at Parupuk Tabings sub-district Koto Tanggahs district West Sumatra Moorland of year 2011 until 2013 available 13 woman that does to part sue. To the effect of observational it identifies and description is factors that cause of woman does to part sue at Parupuk Tabings sub-district, Koto Tanggahs district, West Sumatra moorland. This research utilize kualitatifs approaching with descriptive type. Data collecting tech is done with interview and studi documents. Analisis is data utilizes model Milles and Huberman. Result of this research that factor that cause of woman does to part sue at Parupuk Tabings sub-district Koto Tangahs district Suamteras Moorland West: 1. husband goes to stay out / family, 2. inharmonious that reverential marks sense violence in family (KDRT), 3. economic problem.